Evaluation of Lean Manufacturing Practices in an Automotive Component Manufacturer - Verçosa, Wendeson Rodrigues (2022)
Purpose: This study aims to evaluate lean manufacturing (LM) practices used in a company in the automotive component industry located in Polo Industrial de Manaus (PIM), a manufacturing hub in the city of Manaus. Theoretical framework: The AME Lean Assessment instrument was used as the research framework in this study. This instrument was developed by the Association for Manufacturing Excellence (AME) to benchmark where a company is on its lean journey.Design/methodology/approach: An exploratory case study was carried out, and since a more detailed study was needed, a research framework was used, composed of 14 attributes on lean manufacturing.Findings: The findings point to a high level of LM practices adopted by the company, in addition to allowing the practical application of the fundamental concepts to be observed for the Toyota Production System (TPS) at Polo Industrial de Manaus. The findings have increased the understanding in organizational behavior relating to LM.Research, Practical & Social implications: the study contributes to the body of knowledge on lean manufacturing considering its application in the Amazonian context. The study has made a substantial contribution to the understanding of lean manufacturing in the context of an important industrial park in Brazil. Originality/value: Originality is the adoption of a research framework for evaluating lean manufacturing practices in an Amazonia context, allowing the specific characteristics of lean manufacturing to be understood in Amazonia, from an in-depth case.Keywords: Lean manufacturing; Lean Assessment; Industry; Automotive components; Amazonas.